Structural Inequities in Medicine that Contribute to Racial Inequities in Asthma Care - Okelo, Sande O. (Seminars in Respiratory and Critical Care Medicine, 2022)
Structural inequities in medicine have been present for centuries in the United States, but only recently are these being recognized as contributors to racial inequities in asthma care and asthma outcomes. This chapter provides a systematic review of structural factors such as racial bias in spirometry algorithms, the history of systemic racism in medicine, workforce/pipeline limitations to the presence of underrepresented minority health care providers, bias in research funding awards, and strategies to solve these problems.
Keywords: asthma; spirometry; systemic racism; workforce/pipeline; research funding inequities; strategies